Prevalence of Dirofilaria immitis in the carnivores and its vectors in Mymensingh municipal area of Bangladesh (Research in Agriculture Livestock and Fisheries, 2019)
Heartworm is a global problem caused by Dirofilaria immitis that occurs in some carnivores in tropics and subtropics including some temperate countries. There is also a public health implication, since infection in human is occasionally reported. We investigated the prevalence of D. immitis among carnivores and to identify its vectors and to correlate between them in the study area. We examined the prevalence of D. immitis in stray dogs, wild foxes, and community cats, and in their vectors in Mymensingh Municipal Area. In this study, following the guidelines of the animal welfare and experimentation ethical committee, euthanized animals and mosquitoes were investigated for adult parasites and microfilariae, respectively. Among animals investigated 56.0% of dogs and 71.4% of foxes and none of cats were infected with D. immitis. Infection in animal below 2 years of age were 46.1% and 66.6% in dogs and foxes respectively compared to 66.6% and 75.0% infection respectively in dogs and foxes above 2 years of age. In male the rate of infections were 61.5% in dogs and 75.0% in foxes compared to 50.0% in female dogs and 66.66% in female foxes. Microfilariae were detected in 44% dogs and 57.14% foxes examined. The Culex sp. had 11.3% and the Anopheles sp. had 6.1% infection, whereas none of the Aedes sp had any microfilariae. Since these dogs and foxes live near the human habitations in study area, it was considered a serious public health threat to humans. Because of both veterinary and public health significance, further detailed studies on the prevalence of D. immitis in Bangladesh are highly emphasized.Res. Agric., Livest. Fish.6(2): 315-322, August 2019